2007
DOI: 10.32800/abc.2007.30.0083
|View full text |Cite
|
Sign up to set email alerts
|

Convergences and divergences between two European mountain dung beetle assemblages (Coleoptera, Scarabaeoidea)

Abstract: We analyzed the altitudinal change in dung beetle species richness and the relative proportion of higher taxa, as well as the turnover in the type of distribution and range size of species in two mountain chains located at the two extremes of Europe (Western Rhodopes Mountains and the Iberian Central System). Both mountain ranges showed a clear substitution among higher taxa (Aphodiinae-Geotrupinae vs. Scarabaeidae) and species richness variation with the altitude was similar. We suggest that East European dun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Smaller species compensate for their size by many individuals to achieve the same level of functional efficiency as larger species, hence the combination of the criteria size (or weight) and number of individuals to identify the core and satellite groups. The organization of dung beetle communities in the Middle Atlas, characterized by very few dominant species at the same time, is like those observed in the mountains of alpine areas [23,30,[46][47][48], as well as in Mediterranean environments [29,46,47,[51][52][53][54][55], and in North America [32,49,56].…”
Section: Discussionmentioning
confidence: 64%
“…Smaller species compensate for their size by many individuals to achieve the same level of functional efficiency as larger species, hence the combination of the criteria size (or weight) and number of individuals to identify the core and satellite groups. The organization of dung beetle communities in the Middle Atlas, characterized by very few dominant species at the same time, is like those observed in the mountains of alpine areas [23,30,[46][47][48], as well as in Mediterranean environments [29,46,47,[51][52][53][54][55], and in North America [32,49,56].…”
Section: Discussionmentioning
confidence: 64%
“…We found that elevation acted positively on aphodiines, thus contrasting with hypothesis 6. Previous research showed that the relationship between dung beetle diversity and elevation may show a decreasing pattern (e.g., [85,91,93,94,96,144,145]), a mid-elevation peak [98], or a lack of relationship [99]. Also, previous research showed that elevational range was not an important predictor of dung beetle richness compared to climatic factors [141,146,147].…”
Section: Discussionmentioning
confidence: 99%
“…(6) Elevation influences dung beetle richness negatively. Dung beetle diversity tends to decline with increasing elevation [1,85,[87][88][89][90][91][92][93][94][95][96][97], although mid-elevation peaks [89,91,98] or a lack of relationship have been also reported [85,99]. Not only at higher elevations temperatures might be too low, especially in winter, but the drying effects of increased windiness and insulation might lead to the rapid desiccation of excrements, especially in the summer, when precipitation may be completely absent [85].…”
Section: Introductionmentioning
confidence: 99%